Exploring Nevus Lipomatosis: Case Studies of a Rare Cutaneous Anomaly - Monica Puri; Neelam Gupta (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
Nevus lipomatosis cutaneous superficialis is a rare benign skin condition with an excellent prognosis following surgical excision. In this chapter, we present a case series of four instances of this uncommon anomaly to enhance awareness and recognition of the disease.